Novel insights into pathomechanisms of retinal neuronal degeneration and reactive gliosis in a murine model of GM1-gangliosidosis - Lorna Jubran; Rouven Wannemacher; Anastasiia Ulianytska; Ingo Gerhauser; Wolfgang Baumgärtner; Eva Leitzen (Scientific Reports)
Abstract GM1-gangliosidosis is a lysosomal storage disease characterized by the accumulation of GM1 ganglioside in neurons, including retinal ganglion cells (RGCs). Although vision impairment and retinal degeneration are well-known manifestations in humans, knowledge about the underlying mechanism of these lesions is limited. Pathological retinal changes in a Glb1 knockout (Glb1 −/−) mouse model were assessed using immunohistochemistry, immunofluorescence and transmission electron microscopy in 4- and 7-month-old wild type and Glb1 knockout (Glb1 −/−) mice. Increased numbers of glial fibrillary acidic protein (GFAP) positive Müller cells (MCs) were detected in Glb1 −/− mice both at 4 and 7 months of age, indicating glial reactivity. A transient increase in glutamine synthetase (GS) positive MCs at 4 months of age with a subsequent decrease by 7 months, most likely related to reduced expression of GS, was also observed. Immunohistochemistry revealed loss of RGCs, storage material accumulation and decreased BRN3A expression in 7-month-old Glb1 −/− mice. Increasing numbers of Iba1-positive microglia/macrophages were detected in Glb1 −/− mice at both time points. Microglia/macrophages showed migration towards the inner retinal layers and acquired a morphological phenotype that indicates activation. The present study shows that the murine GM1 model used in this study is suitable for investigating ocular changes in lysosomal storage diseases.